Pengaruh Gaya Kepemimpinan dan Komunikasi Kerja Terhadap Kinerja Karyawan - Kurnia, Beda Atma (Jurnal ATAMA, 2022)
The background of this research is related to the lack of attention from the leadership to their employees. Currently, the problem in the company is that the leadership is not good enough in carrying out supervision, as well as the lack of clarity of the leadership in giving work assignments to employees, and the lack of communication between the leadership and employees in conveying information and work assignments decisions so that miscommunication occurs which results in problems that have an impact on employees performance. This study aims to find out how much influence leadership style and work communication have on employee performance PT Mitra Karya Aluminium. The population in this study were all employees of PT Mitra Karya Aluminium Bandar Lampung as many as 35 employees and determining the number of samples using saturated samples so that the number of samples was 35 respondents. The method used in this research is the casual associative method with quantitative approach. The results showed that the leadership style variable (X1) and effect on employee performance (Y) partial KD of 33,3% and work communication variable (X2) had an effect on employee performance (Y) partial KD of 20,3%. So the result of the total percentage of the influence of variable (X1) and variable (X2) on the variable (Y) is KD R-square of 54%. As of the remaining 46% influenced by other variable not involved in this study.